Odpowiedź:
a)
[tex]\left(-2\frac{3}{5} \right) \cdot 3\frac{1}{8} + \frac{7}{8}=\left(-\frac{13}{5} \right) \cdot \frac{25}{8} +\frac{7}{8} = -\frac{13}{8} \cdot \frac{5}{8} +\frac{7}{8} =-\frac{65}{8} +\frac{7}{8} =-\frac{58}{8} =7\frac{2}{8} =7\frac{1}{4}[/tex]
b)
[tex]-3\frac{1}{2} \cdot \left(-\frac{2}{3} \right) + \left(\frac{3}{4} \right)^2 = -\frac{7}{2} \cdot \left(-\frac{2}{3} \right) + \frac{9}{16} = \frac{14}{6} + \frac{9}{16} = \frac{112 + 27}{48} = \frac{139}{48} = 2\frac{43}{48}[/tex]